PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM KEGIATAN DAKWAH: Analisis Peran Mahasiswa KPI Al-Fatah - Rukanda Sastra Gunawan (Jurnal Komunikasi dan Media, 2025)
Instagram is so familiar with the daily activities of students, in fact, many of them must open Instagram every day. The purpose of this study is to find out how KPI STAI Al-Fatah Cileungsi Bogor students use Instagram as a medium for da'wah. This study is a qualitative study with a descriptive approach. The research sample was Islamic Communication and Broadcasting Students at STAI Al-Fatah Cileungsi Bogor who use Instagram and access Islamic messages on Instagram. The research sample was determined by random sampling. The data collection techniques used observation, interviews and documentation. The data obtained was then analyzed descriptively by means of data reduction, data presentation and drawing conclusions. The results of the study show that Instagram provides many benefits as a medium of da'wah. In utilizing Instagram as a medium of da'wah for KPI students, there are two types of utilization: 1) Utilization of Instagram as a medium of communication, 2) Utilization of Instagram as a medium of da'wah. The conclusion of this study is that students use it as a medium to convey da'wah messages and as access to the da'wah messages themselves.